(untitled) (International Journal of Engineering and Computer Science, 2013)
Distributed Information SHaring (DISH) is a new cooperative approach to designing multichannel MAC protocols. It aids nodes in their decision making processes by compensating for their missing information via information sharing through neighboring nodes. This approach was recently shown to significantly boost the throughput of multichannel MAC protocols. However, a critical issue for ad hoc communication devices, viz. energy efficiency, has yet to be addressed. In this paper, we address this issue by developing simple solutions that reduce the energy consumption without compromising the throughput performance and meanwhile maximize cost efficiency. We propose two energy-efficient strategies: in-situ energy conscious DISH, which uses existing nodes only, and altruistic DISH, which requires additional nodes called altruists. We compare five protocols with respect to these strategies and identify altruistic DISH to be the right choice in general: it 1) conserves 40-80 percent of energy, 2) maintains the throughput advantage, and 3) more than doubles the cost efficiency compared to protocols without this strategy. On the other hand, our study also shows that in-situ energy conscious DISH is suitable only in certain limited scenarios.